The Reasons for Secondary School Students Dropping Out: The Teachers' Point of View - Rababa, Elham Mahmoud; AL-Momani, Mohammad Omar (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
Students dropping out has become a serious attention recently, particularly in the third world countries. Many notions have addressed the main factors which underlies such a phenomenon. This study, therefore, aimed to identify the reasons for secondary school students in Jordan dropping out of their schools from the teachers’ point of view. In this sense, the teachers’ perspective was necessary to obtain overall depictions related to behind reasons of students’ dropping out. The descriptive approach was used in addition to the use of the questionnaire as a study tool. The study sample consisted of 150 secondary school teachers in Ajloun Governorate, Jordan. The study was held in the first semester of the academic year 2021-2022 AD. Based on the data, the study concluded that there were 16 reasons for students dropping out of their schools to a high degree, and 6 reasons leading to students dropping out of their schools to a moderate degree, and 4 reasons leading to students dropping out of their schools to a low degree.